In Vivo Rodent Cervicothoracic Vasculature Imaging Using Photoacoustic Computed Tomography - Junsoo Lee; Hoseong Cho; Sungjo Park; Jaeyul Lee; Daewoon Seong; Ruchire Eranga Wijesinghe; Sangyeob Han; Shinheon Kim; Mansik Jeon; Jeehyun Kim (Photonics, 2021)
Mice and rats are rodent specimens commonly used in multidisciplinary research. Specifically, vasculature imaging of rodents has been widely performed in preclinical studies using various techniques, such as computed tomography, magnetic resonance imaging, and ultrasound imaging. Photoacoustic CT (PACT) is a noninvasive, nonionizing optical imaging technique derived from photoacoustic tomography and benefits from using intrinsic endogenous contrast agents to produce three-dimensional volumetric data from images. In this study, a commercial PACT device was employed to assess the cervicothoracic vasculature of mouse and rat specimens, which has rarely been examined using PACT, under two conditions with depilation and skin incision. Various blood vessels, including the common carotid artery, internal/external jugular veins, cranial vena cava, internal thoracic vein, and mammary, were identified in the acquired PACT images. The difference between the depilated and skin-incised specimens also revealed the presence of branches from certain blood vessels and specific anatomical features such as the manubrium of the sternum. This study presents detailed PACT images observing the cervicothoracic vasculature of rodent specimens and is expected to be used as a reference for various preclinical experiments on mice and rats.